RFID Based Toll Automation System - Shah, Kerav; Inani, Gourav; Rupareliya, Darshan; Bagwe, Rupesh; Bharathi, HN (International Journal of Computer Sciences and Engineering, 2025)
Radio Frequency Identification (RFID) is an auto-identification technology which uses Radio Frequencies (between 30 kHz and 2.5GHz) to identify objects remotely. The automated toll collection system using Radio Frequency Identification (RFID) tag which emerges as a good solution to a manual toll collection system at toll gates. It is used for automatic toll collection at the tollgates and to detect the stolen car at the toll plaza which can help the police to find the stolen car. The RFID tag is a unique ID which is given by the RTO (Regional Transport Office) authority. With respect to these RFID tag ID, all the basic information about the customer and his history is stored. It stores information regarding the tolls, a particular user’s vehicle passes and the amount deducted. The tag detection sensor in the reader creates the electromagnetic medium in which the incoming vehicle’s RFID tag is detected, the toll amount will be deducted from his prepaid balance and the new balance is updated. Time and efficiency are a very major priority of the project in the present day. These make the toll plaza transaction more convenient for the public use, it saves a lot of time and it also helps to conserve the environment by reducing the pollution.